441 Patterns of Food Allergens in Kenyan Children - Kamenwa, Rose (World Allergy Organization Journal, 2012)
BACKGROUND: To determine the patterns of food allergens in children presenting to pediatric gastroenterology clinic at the Aga Khan University Hospital, Nairobi. METHODS: This data includes children evaluated from March to November, 2010.All the children presenting for evaluation of various gastrointestinal symptoms and who had positive history of atopy in at least one first degree relative were included. History of reccurent cough was sought and the skin was examined for eczema. Skin Prick Test was perfomed by an expert in allergy and immunology. Prick to Prick Test was done for local foods where commercial antigens were not available. Positive tests were followed by an exclusion and rechallenge progamme but this was excluded from analysis due to poor compliance. Analysis was performed to determine frequencies and associations of the different gastrointestinal symptoms and food allergens. Both skin Prick and Prick to Prick results were analysed together. RESULTS: The commonest food allergens in order of frequency were cow milk (65%), egg (35%), beef (26%), beans (14%), chicken, corn, wheat, soya and rice (9%), fish (8%) and peanut (5%).Common local infant complementary foods including potatoes, bananas and vegetables all tested positive in 4% of the children. Pumpkin tested positive in one infant who had presented with rectal bleeding. Majority of the children had positive tests to multiple foods. Only 14% of the children had negative tests. The commonest gastrointestinal (GI) symptoms were abdominal pain (38%), constipation (36%), vomiting (14%), diarrhoea (11%), failure to thrive (9%) and colics (3%). Majority of the children had multiple GI symptoms. Eczema and cough were associated symptoms in 9% and 3% of the children respectively. CONCLUSIONS: The prevalence of food allergy as suggested by this study is high in Kenyan children and contributes signficantly towards gastrointestinal morbidity. While cow milk, egg and beef are the commonest allergens, the emerging allergy to local infant complementary foods is also significant. The high frequency of multiple allergens partly contributed to poor compliance in the exclusion rechallenge programme due to lack of options on alternative foods.